The effect of debt securities issuance towards equity market behavior in Malaysia - Chin, Sze Kim; Abdullah, Nur Adiana Hiau (World Business Institute Australia, 2011)
The study investigates the impact of debt securities issuance on equity market behaviour of the issuers. The event study results reveal that overall debt securities issuers experience increase in equity return following debt securities issuance and decrease in systematic risk while total risk remain unchanged.Further examination of the 100 debt securities issuing companies found significant differences between hybrid and non-hybrid debf securifies issues. Hybrid debt securities experience significant fall in equity returns and systematic risk but an increase in total risk.Non-hybrid debt securities issues, however; are found to have no impact on equity market behaviour. Findings of the study imply that general decline in systematic risk for debt securities issuing company could motivate issuance of debt securities and thus improve market liquidity.Further; non-hybrid debt securities are not appropriate to be used for market signal as no impact on market behaviour was found following the issuance.